KECENDERUNGAN SETENGAH PENGANGGUR PERDESAAN MENURUT KARAKTERISTIK INDIVIDU DAN PEKERJAAN - Ahmad Ayis; Lilik Sugiharti (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2021)
The problem in the labor sector of a country is not only unemployment. Underemployment also needs attention, because this is a picture of whether the labor market is efficient or not. The purpose of this study was to analyze the influence of people and their occupation on the chances of being underemployed in rural areas of Central Java. The analysis in this study was carried out using the binary logistic regression method on the SAKERNAS August 2019 data. The unit observation in this study was the working population aged 15-65 years. The results showed that a female worker, youth, and no education or not completing basic education had the highest chance of being underemployed in rural Central Java. Furthermore, part of the rural unemployed can also be seen by their work. A worker in a business field, working in the informal sector, and government and private institutions has a greater chance of being underemployed. In general, job training and work experience have not been able to reduce the chances of becoming unemployed in rural Central Java.